Regional differences in the validity of self-reported use of health care in Belgium: selection versus reporting bias. Issue 1 (December 2016) - Van der Heyden, J.; Charafeddine, R.; De Bacquer, D.; Tafforeau, J.; Van Herck, K.
Abstract Background The Health Care Module of the European Health Interview Survey (EHIS) is aimed to obtain comparable information on the use of inpatient and ambulatory care in all EU member states. In this study we assessed the validity of self-reported information on the use of health care, collected through this instrument, in the Belgian Health Interview Survey (BHIS), and explored the impact of selection and reporting bias on the validity of regional differences in health care use observed in the BHIS. Methods To assess reporting bias, self-reported BHIS 2008 data were linked with register-based data from the Belgian compulsory health insurance (BCHI). The latter were compared with similar estimates from a random sample of the BCHI to investigate the selection bias. Outcome indicators included the prevalence of a contact with a GP, specialist, dentist and a physiotherapist, as well as inpatient and day patient hospitalisation. The validity of the estimates and the regional differences were explored through measures of agreement and logistic regression analyses. Results Validity of self-reported health care use varies by type of health service and is more affected by reporting than by selection bias. Compared to health insurance estimates, self-reported results underestimate the percentage of people with a specialist contact in the past year (50.5 % versus 65.0 %) and a day patient hospitalisation (7.8 % versus 13.9 %). Inversely, survey results overestimated the percentage of people having visited a dentist in the past year: 58.3 % versus 48.6 %. The best concordance was obtained for an inpatient hospitalisation (kappa 0.75). Survey data overestimate the higher prevalence of a contact with a specialist [OR 1.51 (95 % CI 1.33–1.72) for self-report and 1.08 (95 % CI 1.05–1.15) for register] and underestimate the lower prevalence of a contact with a GP [ORs 0.59 (95 % CI 0.51–0.70) and 0.41 (95 % CI 0.39–0.42) respectively] in Brussels compared to Flanders. Conclusion Cautiousness is needed to interpret self-reported use of health care, especially for ambulatory care. Regional differences in self-reported health care use may be influenced by regional differences in the validity of the self-reported information.